Postoperative pain ıntensity after single- versus two-visit nonsurgical endodontic retreatment: A randomized clinical trial - Erdem Hepşenoğlu, Yelda; Eyüboğlu, Tan Fırat; Özcan, Mutlu (Elsevier Science Inc, 2018)
Introduction: The aim of this study was to evaluate postoperative pain after single-visit and 2-visit non-surgical endodontic retreatments with 2 different intracanal medicaments. Methods: A total of 150 patients with asymptomatic root canal treated teeth in need of nonsurgical endodontic retreatment were randomly divided into 3 groups (n = 50). Patients were selected randomly from among those without preoperative pain. Patients in group 1 (single visit) were treated in a single visit. Patients in group 2 and group 3 were treated in different visits with calcium hydroxide and chlorhexidine (CHX) as intracanal medicaments. The presence of postoperative pain was assessed 1, 2, 3, and 7 days and 1 month after treatment. All 2-visit treatments were completed 1 week after the initial visit. Data were analyzed using the Mann-Whitney U, Kruskal-Wallis, and Pearson chi-square tests (alpha = 0.01, 0.05). Results: Postoperative pain was significantly higher in the CHX group in comparison with the single-visit group (P <= .05) on the first day of assessment. On the second day, postoperative pain was significantly less in the single-visit group (P <.05) than in the other 2 groups. There were no significant differences among the groups on the third and seventh days of assessment. At the 1-month assessment, postoperative pain was significantly higher in both the calcium hydroxide group (P <.05) and the CHX group (P <.05) in comparison with the single-visit group. Conclusions: Single-visit nonsurgical endodontic retreatment presented fewer incidences of postoperative pain in comparison with 2-visit nonsurgical endodontic retreatment based on assessments ranging from 1 day to 1 month.
WOS: 000444527700001
PubMed ID: 30054099
Keywords: Intracanal Medicament; Multiple-Visit Root Canal Treatment; Postoperative Pain; Retreatment; Single-Visit Root Canal Treatment